Two nonallelic insulin genes in Xenopus laevis are expressed differentially during neurulation in prepancreatic embryos. - Shuldiner, A R (1991)
Insulin, traditionally regarded as a metabolic hormone, also can potently stimulate growth and differentiation in many cell types. To study further the potential role of insulin during early embryogenesis, we have used the amphibian Xenopus laevis, a versatile model of vertebrate development. Using (i) nucleotide sequences of two previously cloned cDNAs that correspond to two different nonallelic Xenopus insulin genes (both of which are expressed in the adult pancreas) and (ii) a modification of the highly sensitive reverse transcription-polymerase chain reaction (RT-PCR) method developed in our laboratory, designated RNA template-specific PCR (RS-PCR), we now find that mRNAs for both Xenopus insulins I and II are present in mature (stage VI) oocytes but not in less-mature oocytes (stages I and IV) or in unfertilized eggs. The Xenopus insulin II gene is differentially expressed during early neurulation (stage 13), while only the insulin I gene is expressed at stage 21, when the neural tube is closing and cephalization is beginning. During later stages (i.e., stage 26) there is a region in the head that appears to be transcribing only the insulin I gene, while mRNAs for both insulins I and II are present in the body region. These findings show that the two nonallelic insulin genes are expressed differentially in Xenopus embryos in a stage- and region-specific manner; because appropriate receptors are also present, we suggest a role for insulin during early nervous system development well before the emergence of pancreatic beta cells.